PERANCANGAN MEDIA PEMBELAJARAN BERBASIS TIKTOK PADA MATA PELAJARAN TIK DI MTSN 2 KOTA PAYAKUMBUH - Firza, Seni Oknora; Sesmiarni, Zulfani (Indonesian Research Journal on Education, 2022)
The background for designing TikTok-Based Learning Media is the lack of interest and attention of students in learning, and students using the TikTok application just for fun and not using the TikTok application for learning so that they spend more time playing games than studying. This research was conducted at MTsN 2 Payakumbuh. This research method is Research and Development (R&D) with the Luther-Sutopo version of the MDLC (Multimedia Development Life Cycle) development model which consists of 6 stages, namely conceptualization, design, materialcollection, manufacturing process, testing and distribution. While the design of TikTok-BasedLearning Media was made using Articulate Storyline, Camtasia, and the TikTok application itself. The results of this study are TikTok-Based Learning Media products in the form of videos. With the results of the validity test of 0.86 which was declared valid, the results of the Practicality test of 0.92 which were declared very practical, and the results of the effectiveness test of 0.85 which were declared very effective. So it can be concluded that TikTok-Based Learning Media as alearning media is valid, practical and effective. So it can be concluded that the TikTok-BasedLearning Media used as a learning medium is valid, practical and effective.